Analysis of early and deferred clearance at Callao Maritime Customs Agency 2015-2018 - Alvarez Aroni, Juan (2020)
Objective: Study the times used during the merchandise import process by means of anticipated and deferred clearance at the Callao Maritime Customs Office during the period 2015-2018. Method: The research is framed within the deductive method. Information collected on the time of the logistics chain of import of goods in the periods 2015 - 2018 through the Intendancy of Maritime Customs of Callao, which was analyzed using the Kolmogorov - Smirnov test, in order to determine its normality and used the predictability equation. Results: Analyzed the times used in the import process in the modality of anticipated and deferred dispatch, it is verified which sections of the logistics chain explain the behavior of this, which allows creating a behavior predictability equation. Conclusions: The deferred clearance modality has better times in the process of importing merchandise, so the Customs Administration must formulate strategies in order to improve early clearance as it is mandatory for use from 2020.